Hubungan Pengetahuan Ibu tentang MP-ASI dan Jenis Pemberian MP-ASI dengan Status Gizi Balita Umur 6-24 Bulan - Nurkila Syuaib; Inayyah Azzahra; Nur M Ali; Nizmawaty Amra; Nofiandri Nofiandri (Poltekkes Kemenkes Padang, 2024)
The prevalence of children with stunting nutritional status in Ternate in 2021 was 17.7% and children with malnutrition status were 15.2%. The purpose was to analyze the relationship between maternal knowledge about providing complementary feeding with the nutritional status of toddlers aged 6-24 months. This type is an Analytical Survey with a cross-sectional design. This study was conducted in August-September 2024. The research instruments used were Questionnaires, 24-hour Food Recall forms, Length boards, Baby scales. The sample were mothers with toddlers aged 6-24 months and living in Kastela Village, Jambula Health Center Work Area, Ternate Island, as many as 30 toddlers. The sampling technique used in this study was Total Sampling, which was 30 toddlers. To see the relationship between variables, the Spearman rank test was carried out. The findings show that there is a relationship between knowledge and nutritional status based on Weight/Age (0.020), Length/Age (0.029), Weight/Length (0.007) < 0.05. The findings also show that there is a relationship between the type of complementary feeding and the nutritional status of toddlers based on Weight/length (0.011), Weight/Age (0.029) < 0.05. In conclusion, there is a relationship between knowledge and the type of complementary feeding and the nutritional status of toddlers with all nutritional status criteria. This shows the importance of the role of knowledge and the type of complementary feeding in maintaining the nutritional status of toddlers.